Premorbid and current intellectual performance reflects different backgrounds in patients with Parkinson's disease - Hidetomo Murakami; Machiko Kezuka; Junnosuke Ozawa; Kaoru Matsuoka; Tatsuya Nakanishi; Atsushi Ishida; Naohito Ito; Mizuki Kanemoto; Mitsuru Kawamura (Aging and Health Research)
Background: There is growing interest in targeting Parkinson's Disease (PD) at an earlier stage, especially before emergence of motor symptoms. Cognitive dysfunction is a non-motor symptom in PD, whereas the Japanese version of the National Adult Reading Test (JART) is a validated battery to estimate the premorbid intellectual quotient (IQ). Therefore, the results of JART and current cognitive assessment after onset of PD may reflect different background factors. The goal of the study was to compare factors correlated with estimated premorbid intellectual performance using JART and current cognitive function after onset of PD. Methods: Current motor symptoms (Unified Parkinson's Disease Rating Scale; UPDRS Part III) and cognitive function (Montreal Cognitive Assessment; MoCA) were assessed in 48 patients with PD. Premorbid IQs (verbal IQ: VIQ, performance IQ: PIQ, and full scale IQ: FIQ) were estimated using JART. Spearman correlation coefficients were calculated for background factors (current age, years of education, UPDRS Part III, and levodopa equivalent dose of prescribed drugs (LED)) with MoCA scores and estimated IQs. Results: Estimated VIQ (r = 0.451, p = 0.001), PIQ (r = 0.445, p = 0.002) and FIQ (r = 0.453, p = 0.001) were significantly correlated with years of education that was fixed until adolescence (i.e. 20 s). MoCA was significantly correlated with current age (r=−0.401, p = 0.005) and UPDRS part III (r=−0.374, p = 0.009), both of which continue to progress gradually after onset of PD. In multiple regression analyses, these correlations were significant and independent. Conclusion: Premorbid and current intellectual performance reflect different background factors in patients with PD.